Supplementary Data Table S1 - Hayden Dalton (2022)
This file contains Supplementary Table S1, a table of radiogenic isotope data and geothermometry calculations which supplement the article “ Geodynamic and isotopic constraints on the genesis of kimberlites, lamproites and related magmas from the Finnish segment of the Karelian craton ”. Submitted to Geochemsitry, Geophysics, Geosystems on 30th December 2021